Formulation of Dipyridamole Sustained Release Tablet Using Floating System - Saleh Wikarsa; Lenny Mauilida Mauilida (Makara Journal of Health Research, 2011)
Dipyridamole is a drug for prevention of postoperative thromboembolic complication of heart valve replacement and long term therapy of angina pectoris will be well absorbed in stomach. To maintain therapeutic plasma concentration in long time and to increase bioavalaibility is needed a sustained release dosage form having the long residence time in the stomach. The objective of this research was to make floating sustained release tablet of dipyridamole conforming to the requirement that was set up by dipyridamol therapeutic concentration. Tablets were made by wet granulation method using aquadest as a liquid binder, HPMC K4M, Ac-di-sol, Avicel PH 102, talk, and Mg stearat. Dissolution assay was carried out using type 2 release tester at rotation speed of 50 rpm in medium 900 mL HCl 0.1 N at 337 ± 0.5 °C for 8 hours. The formulation containing of 50 mg dipirydamole, HPMC K4M (30%), Ac-di-sol (20%), Avicel PH 102 (37%), talk (2%), and Mg stearat (1%) released 59.61 ± 6.73% and 89.34 ± 5.87% of dipyridamole respectively after 4 and 8 hours that conformed to the requirement.